National Fiqh and Maqasid-Based Ijtihad: Reassessing Ahmad Hasyim Muzadi through Jamal al-Din ‘Atiyyah - Muhammad Solikhudin; Irzak Yuliardy Nugroho; Moh. Faizur Rohman; Ahmad Rezy Meidina; Ashima Faidati (Universitas Muhammadiyah Bandung, 2025)
This study examines Ahmad Hasyim Muzadi’s concept of fikih kebangsaan (national fiqh) through the lens of Jamal al-Din ‘Atiyyah’s maqāṣid al-sharī‘ah theory. While previous studies have discussed national fiqh primarily in normative and socio-political terms, limited attention has been given to its maqāṣid-based methodological foundation. This article addresses that gap by analyzing how Muzadi’s thought reflects a structured maqāṣidī mode of ijtihad. This research employs a qualitative conceptual approach based on library research, examining primary texts of Ahmad Hasyim Muzadi alongside Jamal al-Din ‘Atiyyah’s maqāṣid framework. The analysis focuses on identifying the epistemological structure and levels of maqāṣid embedded in Muzadi’s formulation of national fiqh. The findings demonstrate that Muzadi’s fikih kebangsaan embodies a maqāṣid-based ijtihad operating across three interconnected dimensions: individual, communal, and humanitarian. His conception positions Indonesian Islam as a harmonizing force within plural society, affirms Pancasila as a constitutional meeting point between religion and state, and frames religious moderation as a strategic instrument for national cohesion. This construction reflects a substantive alignment with Jamal al-Din ‘Atiyyah’s expanded maqāṣid theory, particularly in integrating social welfare, civic solidarity, and national integrity into legal reasoning. The study concludes that Muzadi’s national fiqh represents a contextual maqāṣidī reconstruction of Islamic legal reasoning relevant to contemporary plural societies. It recommends further development of maqāṣid-based national fiqh as a methodological framework for strengthening religious moderation and constitutional harmony in Indonesia.